Existence of immovability lines of a partial mapping of Euclidean space E5 - Matieva, Gulbadan; Abdullayeva, Cholpon; Ahmedov, Anvarjon A. (IOP Publishing, 2019)
It is considered a set of smooth lines such that through a point X ∈ Ω passed one line of given set in domain Ω ⊂ E5. The moving frame is frame of Frenet for the line ω1 of the given set. Integral lines of the vector fields are formed net ∑5 of Frenet. There exists a point on the tangent of the line ∑5. When a point X is shifted in the domain Ω the point describes it's domain in E5. It is defined the partial mapping , such that . Necessary and sufficient conditions of immovability and degeneration of lines and in partial mapping are obtained.